CULTURAL SILENCE: UNVEILING PITUITARY APOPLEXY IN A MAN WITH CHRONIC ERECTILE DYSFUNCTION AND COEXISTING PROSTATIC ABSCESS - Anuar, Mohamad Azeri Bin Mohd; Rasidi, Nur Iffah Illani Binti Mohamed; Huan, Puah Soo; Shean, Wong Poh; Aziz, Fauzi Azizan Bin Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Pituitary apoplexy is an endocrine emergency caused by hemorrhage or infarction within a pituitary tumor, resulting in acute pituitary dysfunction. Triggers can include major surgeries, angiography, intracranial hypertension, or distant infections. In this case, fever and signs of increased intracranial pressure revealed a previously undiagnosed pituitary macroadenoma, initially presenting as chronic erectile dysfunction, which ultimately led to a diagnosis of pituitary apoplexy. CASE A 43-year-old male with obstructive sleep apnoea presented with acute fever, vomiting, headache, postural dizziness, and lethargy. He had long-standing erectile dysfunction, previously uninvestigated. Initially treated for gastroenteritis, he was drowsy (Glasgow Coma Scale, GCS: Eye 3, Verbal 4, Motor 6), with left temporal hemianopia but no signs of meningism or focal neurological deficits. Laboratory tests showed leukocytosis (12 × 10⁹/L) predominantly neutrophilia, elevated C-reactive protein (105 mg/L), hyponatremia (125 mmol/L), hypokalemia (3 mmol/L) and negative blood cultures. Abdominal ultrasonography revealed a small prostatic abscess. Neuroimaging (CT brain and MRI pituitary) confirmed a pituitary macroadenoma (2.0 × 2.9 × 3.7 cm) with hemorrhagic apoplexy compressing the optic chiasm. Hormonal evaluation showed secondary hypogonadism, hypocortisolism, and hypothyroidism. Treatment with antibiotics and intravenous hydrocortisone, followed by thyroxine and testosterone therapy, resulted in clinical improvement, including resolution of the prostatic abscess, visual field deficit, and erectile dysfunction. Follow-up imaging showed a decrease in the size of the sellar mass (1.5 × 1.7 × 1.5 cm), hence the neurosurgery team opted for conservative management with continued endocrine follow-up. CONCLUSION The importance of addressing male sexual dysfunction without stigma is highlighted by this case. Non-functioning pituitary macroadenomas commonly affect the hypothalamic-pituitary-gonadal axis, and concurrent fever may mask an underlying infection. This infection, in turn, could trigger pituitary apoplexy. Clinicians should maintain a high index of suspicion and intervene promptly in patients presenting with elevated intracranial pressure to ensure optimal outcomes.